2016
DOI: 10.4314/sokjvs.v14i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of lesions in the gastrointestinal tract of buffalo (<i>Bubalus bubalis</i>) calves orally exposed to <i>Pasteurella multocida</i> B:2

Abstract: The gastrointestinal lesions and bacterial distribution of buffalo calves were evaluated histologically using immunoperoxidase, following oral exposure to wild-type Pasteurella multocida B:2 at 10 9 cfu/mL in phosphate buffered saline. The lesions were basically of mild to severe mucohaemorrhagic abomasitis and enteritis.The lesions were confirmed to be associated with the inoculated P. multocida B:2, using the immunoperoxidase technique. P. multocida B:2 antigen was detected not only in the bacterial clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…There is some evidence from the 2015 outbreak that invasion also occurred through the gut (Kock et al 2018), a phenomenon also observed in infection studies in ruminants (Abubakar et al 2016). So a link to forage and vegetation cannot be ruled out.…”
Section: Future Researchmentioning
confidence: 98%
“…There is some evidence from the 2015 outbreak that invasion also occurred through the gut (Kock et al 2018), a phenomenon also observed in infection studies in ruminants (Abubakar et al 2016). So a link to forage and vegetation cannot be ruled out.…”
Section: Future Researchmentioning
confidence: 98%